Learning Independence and Educational Social Media Use in Relation to Mathematical Critical Thinking Among Junior High School Students - Dhea Tri Fadillah; Muhammad Nuh (Universitas Wiralodra, 2026)
Improving students' mathematical critical thinking has become one of the central priorities in mathematics education. However, limited evidence has examined the combined contribution of learning independence and educational social media use among Indonesian junior secondary students. The relationships among the variables were examined through a quantitative correlational study that included all 122 eighth-grade students using the total sampling method. Data collection relied on validated questionnaires and a mathematical critical thinking assessment, while the analysis employed Pearson correlation and multiple linear regression techniques. The results showed that learning independence (r = .407, p < .001) and educational social media use (r = .435, p < .001) were both positively associated with mathematical critical thinking. Together, both variables explained 34.6% of its variance (R² = .346, p < .001). These findings provide empirical evidence that learning independence and educational social media use complement each other in supporting mathematical critical thinking and suggest that mathematics instruction should integrate self-regulated learning with purposeful educational technology use.